Effect of Project High Five, a peer education intervention program in the KAP & compliance for voluntary counseling and testing for HIV of a University in Iloilo City - Celiz, Ela Marie Sofia; Estrella, Anjelou Marie B.; Martin, Snow Conception T.; Samson, Mary Camille T.
The present study sought the effectivity of ?Project High Five?, a peer-led intervention program about HIV & AIDS awareness, in the knowledge, attitude and practice toward HIV and compliance to voluntary counseling and testing for HIV among 16-25 years old university students. National & Regional HIV Situationer and Department of Health (2016) stated that the total number of cases in Region 6 is 1,211, 92% male cases and 8% for female cases, in which 284 (23.45%) are youth ages 15-24 years old. These were mostly transmitted through sexual contact. Peer education has been found to be effective in changing adolescents? knowledge, attitude & risky behaviour toward HIV and AID (Bulduk & Erdogan, 2012). The target school for this intervention is PHINMA-University of Iloilo situated in Iloilo City, Philippines. After Project High Five was implemented, it was observed among 384 college students eligible for assessment, using Wilcoxon Signed Rank test, that the knowledge, -15.737 (p<0.001), attitude -14.887 (p<0.001), of students improved significantly. From low to average knowledge of HIV, slightly positive attitude toward AIDS and low to moderate risk of practicing risky behaviour. When it comes to compliance, using McNemar?s test and Chi-square test, it was found out that the students have complied very well, 135.005 (p<0.001), with a change of ?no? to ?yes? when asked if they were willing to get tested. In addition, those who said yes have signed a testing pledge to get tested eventually if not after the intervention. In addition to this age, sex, religion, income and relationship status have been correlated to KAP toward HIV & AIDS & compliance to VCT for HIV and it was found that women have more knowledge at baseline and people who have below P50,000 income have negative attitude and more risky behaviour. This study has proven the effectivity of Project High Five as a peer education approach focusing on HIV & AIDS and the researchers recommend to add HIV & AIDS related courses in college curriculum and utilize Project High Five to innovate appropriate intervention among different groups with regards to HIV & AIDS awareness.